2022
DOI: 10.3389/fpsyg.2022.1020764
|View full text |Cite
|
Sign up to set email alerts
|

Where there is pressure, there is motivation? The impact of challenge-hindrance stressors on employees’ innovation performance

Abstract: Based on the conservation of resource theory, this manuscript explores the impact mechanism of the challenge and hindrance stressors on innovation performance, introduces emotional atmosphere as a mediation variable, and on this basis, it examines the moderating role of organizational climate on emotional atmosphere and innovation performance. A two-wave survey of 263 subordinates and 29 supervisors who come from multisource field offered support for our model. Results showed that challenge stressors have a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
4
0
1
Order By: Relevance
“…Recent studies have primarily focused on the concept of challenge stress, which refers to a type of stress that can promote personal growth and achievement [6]. Several studies have established a positive correlation between stress induced by challenges and innovative behavior [7,8]. Nevertheless, some researchers have proposed that the dynamics of this relationship may exhibit greater complexity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have primarily focused on the concept of challenge stress, which refers to a type of stress that can promote personal growth and achievement [6]. Several studies have established a positive correlation between stress induced by challenges and innovative behavior [7,8]. Nevertheless, some researchers have proposed that the dynamics of this relationship may exhibit greater complexity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies found that age, gender, educational level, and organizational tenure were significantly related with innovation performance ( Fischer et al, 2019 ; Rangus and Cerne, 2019 ; He et al, 2020 ; Dou et al, 2022 ; Zhong et al, 2022 ) and time pressure ( Skerlavaj et al, 2018 ; Urbach and Weigelt, 2019 ). In order to make the effect of time pressure on innovation performance estimated more precisely, we included these variables as control variables, including employee’s age (Mean = 28.338, SD = 3.096, range from 21 to 50 years), gender (0 = male, 1 = female), educational level (1 = junior college degree or below, 2 = bachelor’s degree, and 3 = master’s degree or above), and organizational tenure, which was measured as the number of working years spent in the current organization (Mean = 4.15, SD = 2.42, range from 1 to 20 years).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, role ambiguity and absence of precise information regarding work goals leads to increased stress and weakened satisfaction (Cordes & Dougherty, 1993). Employees whose roles and responsibilities are not clear may not engage in creative initiatives (Aydin & Kaya, 2021;Dou et al, 2022). Evidence also indicates that teams which are exposed to stressors are less likely to perform creatively (Razinskas et al, 2022).…”
Section: Relating Hindrance Stressors With Creativity and Burnoutmentioning
confidence: 99%
“…En este sentido, la ambigüedad de la función laboral y la ausencia de información precisa sobre las metas laborales producen un mayor nivel de estrés y menor nivel de satisfacción (Cordes & Dougherty, 1993). Los trabajadores cuya posición y responsabilidades no están definidas con claridad tienden a no participar en iniciativas creativas (Aydin & Kaya, 2021;Dou et al, 2022). La evidencia sugiere que los equipos que están expuestos a estresores son menos tendentes a desenvolverse con creatividad (Razinskas et al, 2022).…”
Section: La Vinculación De Los Estresores Obstáculo Con La Creativida...unclassified